Urban Transport in Asia: An Agenda For The 1990s - Peter Midgley (The Institute for Research and Community Services, Institut Teknologi Bandung, 1993)
Asia is estimated to have had a total population of 2.9 billion inhabitants in 1990 or half the world's population. The vast majority are concentrated in the 16 countries classified as low